Sythesis of tropomyosin in cultures of differentiating muscle cells (The Rockefeller University Press, 1978)
The accumulation of tropomyosin in cultures of differentiating muscle cells was quantitatively measured. Tropomyosin was isolated from cultured cells during and after myoblast fusion; both alpha- and beta- subunits were present in myotube cultures. During fusion small amounts of tropomyosin were detectable, but, as fusion approached a maximum, tropomyosin accumulation began to increase. The increased synthesis of tropomyosin after the initiation of muscle cell fusion is consistent with the increased synthesis of other proteins characteristic of muscle, including myosin.